Study on overlying strata movement characteristics and strata behavior law in long wall paste filling mining - CHEN Yang; LI Changqing; ZHANG Yan; ZHANG Lili; SU Miaomiao; LUAN Boyu (矿业科学学报)
In order to reveal the characteristics of overlying rock migration and mining pressure manifestation in deep well long wall paste filling mining, the 1123 filling working face of Gucheng Coal Mine was taken as the research object, and geological radar, multi-point displacement meter, microseismic monitoring and other methods were used for research. The research results show that: (1) The range of influence of advanced mining in the working face is 33~37 m, and the range of influence of advanced mining on the coal pillar side of the intake roadway increases to 50 m. The range of influence of advanced mining in the fault affected area of the return airway shows an increasing trend; (2) The microseismic events in the filling working face exhibit distribution characteristics such as asymmetry, low energy, low vertical development height, concentrated bottom plate, and dispersed top plate, with a majority of small energy events; (3) The top plate of the filling working face is mainly deformed and sunk, without large-scale damage or major energy events, indicating that filling mining reduces the migration mode and strength of the overlying rock layers; (4) When the progress of filling the working face reached 165.6 meters, there was no significant subsidence on the surface, indicating that filling mining has a good inhibitory effect on surface subsidence.